(untitled) (Universal International Scientific Journal, 2026)
This article focuses on the strategic and tactical goals of teaching subjects based on interdisciplinary connections, developing knowledge in related subjects, improving the learning process, and developing students’ qualities such as free, independent thinking, a conscious attitude to the surrounding reality, and social activity. It shows how to teach demonstrations, laboratory and practical work in physics in grade 7 based on interdisciplinary connections, linking them to production processes and professions.